2019
DOI: 10.14710/nmjn.v9i2.26014
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Women with Cervical Cancer in Indonesia: A Cross-Sectional Study

Abstract: Background: Cervical cancer have significant impacts on the quality of life (QOL) of the women experiencing it. Limited studies are exploring QOL among Indonesian women diagnosed with cervical cancer.Purpose: This study aimed to investigate the QOL of women with cervical cancer who received radiation therapy and chemotherapy. Methods: A cross-sectional study was conducted to evaluate the QOL among 164 women with cervical cancer undergoing treatment. A consecutive sampling technique was used to recruit the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…In all, 49 studies reported the impact of a woman's diagnosis of cervical cancer on social support 13–61 . Social support was most commonly reported through the European Organization for Research and Treatment of Cancer Core Quality of Life questionnaire (EORTC) tool using the categorization of social functioning ( n = 18) 17,19,23,26–28,30,33,34,44,45,48,51,55,57,59 . This category measures how a woman's diagnosis impacts their family and social activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all, 49 studies reported the impact of a woman's diagnosis of cervical cancer on social support 13–61 . Social support was most commonly reported through the European Organization for Research and Treatment of Cancer Core Quality of Life questionnaire (EORTC) tool using the categorization of social functioning ( n = 18) 17,19,23,26–28,30,33,34,44,45,48,51,55,57,59 . This category measures how a woman's diagnosis impacts their family and social activities.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 studies reported on how a woman's diagnosis of cervical cancer impacts her independence 17,19,20,22,23,26–28,30,32–34,37,44,45,48,51,55,57–59,62 . Of the 22 included studies, 19 utilized the EORTC survey tool, which asked women if they were limited in their work and activities 17,19,20,22,23,26–28,30,32–34,44,45,48,51,55,57–59,62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the cervix being a reproductive organ and a characteristic of female gender identity, sexual issues are a common side effect of cervical cancer. For their quality of life to improve following cervical cancer treatment, women must be able to deal with sexual issues (Afiyanti, Wardani, & Martha, 2019). The desire, arousal, lubrication, dyspareunia, and sexual satisfaction domains showed the lowest performance in the group that underwent radical hysterectomy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kanker adalah suatu penyakit yang dialami oleh semua manusia di dunia terutama pada wanita, yaitu kanker serviks (Simanullang et al 2020;Simanullang, S Ilyas, et al 2021;Simanullang and Sitopu 2020) dan kanker payudara dan dari penelitian terdahulu menemukan bahwa salah satu factor ini disebabkan oleh rendahnya tingkat pengetahuan wanita untuk pencegahan kanker (Clarke et al 2018;Simanullang 2018;Simanullang, Syafruddin Ilyas, et al 2021). Kanker payudara adalah salah satu penyakit dan bahkan sampai sekarang tidak diketahui apa penyebabnya (Afiyanti, Wardani, and Martha 2019;Haakensen and D. 2018).…”
Section: Pendahuluanunclassified